Efektivitas Media Pembelajaran Smartbox dalam Meningkatkan Daya Kemampuan HOTS Siswa pada Pembelajaran Matematika Sekolah Dasar - Syarifatur Rofikoh; Jamilatun Nafi'ah (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This research is motivated by the low ability of Higher Order Thinking Skills (HOTS) of students in mathematics learning, which is still dominated by lecture methods and the minimal use of interactive learning media. This study aims to test the effectiveness of smartbox learning media in improving HOTS abilities in fourth grade students of SDS NU Padomasan. The study used a quantitative approach with a one group pretest-posttest design. The research subjects were 30 students. The instrument used was a test that had passed validity and reliability tests. The results of the validity test showed that out of 15 questions, 12 were declared valid and 3 were invalid. Meanwhile, the reliability test obtained a Cronbach's Alpha value of 0.867 which indicates that the instrument has a high level of reliability. The normality test using the Kolmogorov-Smirnov test yielded a significance value of 0.200 (>0.05), indicating a normally distributed data. The results of the hypothesis test using the Paired Sample T-Test showed a significance value of 0.005 (<0.05), indicating a significant difference between the pretest and posttest scores. Furthermore, there was an increase in each HOTS indicator, namely analytical skills (C4), evaluation (C5), and creativity (C6), with a significance value of 0.000. Thus, it can be concluded that the smartbox learning media is effective in improving students' HOTS skills in mathematics learning. This media is also able to create a more active and interactive learning atmosphere, thus helping students understand concepts more deeply.